Fatigue behavior of corroded non-load-carrying bridge weathering steel Q345qDNH fillet welded joints. (August 2020) - Su, Han; Wang, Jian; Du, Jinsheng
Abstract: Fatigue behavior of corroded non-load-carrying fillet welded joints exposed to atmosphere in Nanjing for 1-year which were made of bridge weathering steel Q345qNH was explored in this paper. Fatigue tests were conducted on 8 specimens which were under 8 stress ranges, fitted S-N curve and lower bound of 95% survival probability were established. It was found that fatigue strength dropped by 26.2% after 1-year exposure compared to uncorroded specimens, the design S-N curve for non-load-carrying fillet welded joint in Eurocode 3 is still satisfactory for fatigue assessment of this batch of specimens. Fractography analysis revealed that fatigue cracks always originated from multiple corrosion pits, geometries of corrosion pits were quantified by surface morphology analysis. Numerical simulation of mixed-mode fatigue crack propagation was conducted, it is found that taking the geometry of the deepest pit as the equivalent initial crack and orienting the crack in the direction normal to the maximum tensile stress plane could predict fatigue lives safely and satisfactorily. The research provides reference for design and fatigue assessment of uncoated weathering steel bridges.